Successful treatment of refractory red cell aplasia after allogeneic hematopoietic cell transplantation with daratumumab. (20th November 2019) - Salas, Maria Queralt; Alahmari, Ali; Lipton, Jeffrey Howard
Abstract: Pure red cell aplasia (PRCA) is an uncommon complication secondary to ABO mismatched allogeneic stem‐cell transplantation (allo‐HSCT). The best approach for PRCA after allo‐HSCT remains unclear. We aim to report a single case with refractory PRCA post‐ABO mismatched allo‐HSCT resolved with daratumumab. A 34‐year‐old male diagnosed with aplastic anemia in March 2014 received a peripheral blood reduced‐intensity allo‐HSCT from an HLA‐matched related donor in July 2016. Donor and recipient blood groups were AB positive and 0 positive, respectively, indicating a major ABO incompatibility. The patient was diagnosed with PRCA 2 months after allo‐HSCT. After failing multiple standard lines of treatment, compassionate treatment with daratumumab was requested. After receiving six doses of daratumumab, the patient had a marked reticulocyte response and consecutively become transfusion independent. In conclusion, Daratumumab is a human IgG1κ monoclonal antibody targeting CD38 and is used to treat multiple myeloma. The use of anti‐CD38 therapy with daratumumab to target residual host plasma cells is safe and effective, and it can be considered in refractory recipients with PRCA after allo‐HSCT secondary to ABO incompatibility.